2020
DOI: 10.1093/ejcts/ezaa228
|View full text |Cite
|
Sign up to set email alerts
|

The rapid transformation of cardiac surgery practice in the coronavirus disease 2019 (COVID-19) pandemic: insights and clinical strategies from a centre at the epicentre

Abstract: OBJECTIVES The onset of the coronavirus disease 2019 (COVID-19) pandemic has forced our cardiac surgery programme and hospital to enact drastic measures that has forced us to change how we care for cardiac surgery patients, assist with COVID-19 care and enable support for the hospital in terms of physical resources, providers and resident training. METHODS In this review, we review the cardiovascular manifestations of COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 16 publications
1
31
0
Order By: Relevance
“…More advanced or severe complications in cardiac conditions are currently presenting 43 and may present further post‐pandemic, which may lead to a rise in morbidity and mortality 51 . Delayed care or reluctance of patients to seek medical attention earlier may result in valve disease progressing to symptoms of advanced or decompensated HF 52 …”
Section: Heart Failure Hospitalizationmentioning
confidence: 99%
“…More advanced or severe complications in cardiac conditions are currently presenting 43 and may present further post‐pandemic, which may lead to a rise in morbidity and mortality 51 . Delayed care or reluctance of patients to seek medical attention earlier may result in valve disease progressing to symptoms of advanced or decompensated HF 52 …”
Section: Heart Failure Hospitalizationmentioning
confidence: 99%
“…Clear decision-making processes were facilitated, for example, by clear definitions of “urgent” and efficient channelling of information to create a clear and consistent message (George et al, 2020). For the latter, suggestions included limiting the use of email chains, using Dropbox or apps like Induction of Clinbee, and bespoke WhatsApp groups (NHS England & NHS Improvement, 2020a).…”
Section: Resultsmentioning
confidence: 99%
“…Redeployed staff experienced anxiety and stress, particularly when lacking adequate support, during night shifts when less staff were available, and due to last minute rota changes. Staff wellbeing needs that required attention included accommodation, testing and family responsibilities (D’souza, Shetty, Apuri, & Moreira, 2020; George et al, 2020). Lim et al, (2020) reported that redeployed ophthalmologists’ anxiety reduced once their redeployment role began.…”
Section: Resultsmentioning
confidence: 99%
“…Forced by the implications of the coronavirus disease 2019 (COVID-19) crisis, the staff at the New York Presbyterian Hospital managed to rearrange their system of healthcare delivery to improve conditions to deal with the crisis [ 1 ]. They showed what potential for evolvement lies underneath the surface in a time of need.…”
mentioning
confidence: 99%